Asociación diámetro - altura total y su predicción en el crecimiento de las plantas de Aspidosperma spruceanum "quillobordon" en diferentes dosis de fertilización, Puerto Almendra, Loreto, Perú, 2019 - Díaz Narvaez, Antenor (2022)
The study was carried out in a CIEFOR Puerto Almendra FCF - UNAP plantation, San Juan Bautista, Maynas, Loreto, Peru. The objective was to determine the diameter - total height association and its prediction in the growth of Aspidosperma spruceanum “quillobordon” plants with different doses of foliar fertilization . Plots 5 (band “A1”), 6 (band “F”) and 9 (band “G”) of the plantation were used, with plants without foliar fertilization (control) and plants with foliar fertilization of 40 ml an d 60 ml respectively. The results indicate that the association between diameter and total height for Aspidosperma spruceanum “quillobordon” plants with 40 ml an d 60 ml foliar fertilization and without foliar fertilization, the allometric model that best adjusted was the cubic one; Regarding the association's rating, it was excellent. Regarding the growth of the diameter and height of Aspidosperma spruceanum “quillobordon” plants without foliar ferlization and with foliar fertilization of 40 ml and 60 ml, they present a statistical difference between them, with a 95% probability of confidence, highlighting the growth in the plants. with foliar fertilization.